ISLAM DAN ADAT: TINJAUAN AKULTURASI BUDAYA DAN AGAMA DALAM MASYARAKAT BUGIS - Wekke, Ismail Suardi (Analisis: Jurnal Studi Keislaman, 2013)
Islamic  studies  and adat  (tradition)  tend  to  enhance  discourse to  see how religion  encounters  with  local culture.  Recently,  it shows that  there are harmony and interaction  between  them. In addition,  there  is acculturation in performing  religious practice in daily  life. Therefore,  this  study  will explore  the  interaction between Islam and adat in Bugis society in term culture acculturation.  Qualitative  approach was conducted during circle of research. Non-participant observation  and in-depth  interview were employed in collecting data. This research shows that there is synergetic  on adat understanding  with  religious  expressions. Adeq (adat) and saraq (Islamic law) both were placed as part of panggaderreng (social law). As a result, this combination gathers to rule society life. Moreover, many adat activities adapt to Islam principles. Islam was translated  to local life round in preserving ethnicity existence then transform to belief spirit. Using this local potency convert a strategy to develop spirituality  without Arabic characteristics.  Islam in Bugis adat context  interprets  to  norm and tradition  in expanding  identity  Bugis society.  Finally, adat and religion encounters in Bugis society culture demonstrate  that there was a dialogue between them and construct a new tradition in local environment.